Answer :

PunIntended

Answer:

-5x - 8y = -5

Step-by-step explanation:

Whenever we two equations, we are essentially just adding the left sides up and then the right sides up. Here, let's write these into one whole big equation:

(4x - 4y) + (-9x - 4y) = -2 + (-3)

Taking the parentheses out, we have:

4x - 4y - 9x - 4y = -2 - 3

Combine like terms:

4x - 9x - 4y - 4y = -5

-5x - 8y = -5

Hope this helps!

meep55

Answer:

-8y-5x=-5

Step-by-step explanation:

Tocombine equations add the two sides together.

(4x-4y)+(-9x-4y)=-2+(-3)

4x-4y-9x-4y= -5

-8y-5x=-5

Other Questions